A Novel Silica-Nylon Mesh Reinforcement for Dental Prostheses - Paes-Junior, Tarcisio José De Arruda [UNESP]; De Castro, Humberto Lago [UNESP]; Borges, Alexandre Luiz Souto [UNESP]; Della Bona, Alvaro; Gonçalves, Fernanda De Cássia Papaiz (Hindawi, 2017)
Statement of the Problem. Acrylic resin-based dentures can fracture; thus they can benefit from reinforcement. Purpose. To evaluate the effect of a novel reinforcement structure made of nylon fibers and silica particles on the flexural strength of acrylic resin after relining and aging. Materials and Methods. Bar-shaped specimens were fabricated and divided into the following experimental groups (n=20): control (acrylic resin without reinforcement); acrylic resin nylon fiber-reinforced; acrylic nylon and silica fiber-reinforced; acrylic nylon fiber-reinforced-relined; acrylic nylon and silica fiber-reinforced-relined. Half of the specimens from each group were aged by thermomechanical cycling (10000 cycles between 5°C and 55°C) before flexural strength testing to failure using a universal testing machine. Data (MPa) were statistically analyzed using analysis of variance and Tukey tests (μ=5%). Results. Adding nylon fibers or silica-containing nylon fibers significantly increased the flexural strength of all the groups tested. Within the similar groups processed in the same manner, the relining procedure reduced the flexural strength of the specimens, whereas aging process had no effect on the strength values. Conclusion. Incorporating a silica-containing nylon fiber mesh into acrylic resin yielded the greatest flexural strength for the evaluated structures.